2012
DOI: 10.1371/journal.pone.0040015
|View full text |Cite
|
Sign up to set email alerts
|

MED12 Alterations in Both Human Benign and Malignant Uterine Soft Tissue Tumors

Abstract: The relationship between benign uterine leiomyomas and their malignant counterparts, i.e. leiomyosarcomas and smooth muscle tumors of uncertain malignant potential (STUMP), is still poorly understood. The idea that a leiomyosarcoma could derive from a leiomyoma is still controversial. Recently MED12 mutations have been reported in uterine leiomyomas. In this study we asked whether such mutations could also be involved in leiomyosarcomas and STUMP oncogenesis. For this purpose we examined 33 uterine mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 44 publications
12
109
2
2
Order By: Relevance
“…28,29 Frequent loss of heterozygosity particularly for chromosomes 10 and 13 has been described. 30,31 Recently, the first recurrent somatic mutations of the Mediator Subcomplex 12 gene (MED12) have been demonstrated in benign and malignant uterine 32,33 and extrauterine smooth muscle tumors 34 indicating that MED12 mutations have a crucial role in tumors with smooth muscle differentiation. In addition, Fumarate Hydratase (FH)-deletions and rearrangements of high motility group protein 2 (HMGA2) have been proposed as independent somatic driver mutations in leiomyoma.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Frequent loss of heterozygosity particularly for chromosomes 10 and 13 has been described. 30,31 Recently, the first recurrent somatic mutations of the Mediator Subcomplex 12 gene (MED12) have been demonstrated in benign and malignant uterine 32,33 and extrauterine smooth muscle tumors 34 indicating that MED12 mutations have a crucial role in tumors with smooth muscle differentiation. In addition, Fumarate Hydratase (FH)-deletions and rearrangements of high motility group protein 2 (HMGA2) have been proposed as independent somatic driver mutations in leiomyoma.…”
Section: Introductionmentioning
confidence: 99%
“…Some mutations in leiomyoma are also found in leiomyosarcoma, though the mutations seem rare in malignant tumors (Perot et al, 2012). Moreover, MED12 is expressed in all typical leiomyoma but in only 60% of atypical leiomyoma, 50% of STUMP and 20% of leiomyosarcoma (Perot et al, 2012). These results implicate that while not all leiomyosarcoma and STUMP develop from leiomyomas, a subset of leiomyoma has the potential for malignant progression.…”
Section: Compliance With Ethics Guidelinesmentioning
confidence: 92%
“…These results suggest that the MED12 mutation might be involved in the activation of the Wnt pathway that activates β-catenin, which is known to cause leiomyoma-like lesions in a mouse model. However, immunohistochemistry results showed that there is no correlation between MED12 status and β-catenin nuclear/cytoplasmic localization (Perot et al, 2012;Islam et al, 2013). Therefore, detailed mechanism for how MED12 mutations induce uterine leiomyoma awaits further investigation.…”
Section: Med12 Mutations and Uterine Leiomyomamentioning
confidence: 99%
See 2 more Smart Citations